Terapi pijat sebagai intervensi keperawatan untuk meningkatkan kualitas tidur pada bayi dengan diagnosis medis tuberculosis: case report - Zulia Putri Perdani; Mardika Dwi Setiyani (STIKes Surya Global Yogyakarta, 2021)
Babies who are treated with a diagnosis of tuberculosis (TB) can cause several nursing problems such as respiratory problems, lethargy and sleep disorders. Massage therapy is a form of nursing intervention that can improve sleep quality. The purpose of this study is to inform the effectiveness of massage therapy in tuberculosis infants who were treated with problems with sleep disturbances. This research was a case report. The sampling technique was purposive sampling, and there were 3 babies as a sample. The three babies were babies who have tuberculosis and sleep disorders. The three babies were given massage therapy for 4 days for 15 minutes, and it was done twice a day. Sleep quality was measured before and after massage therapy using the A Brief Screening Questionnaire For Infant Sleep Problems (BISQ) questionnaire. The results showed that there were an increase in the total score of sleep quality in the three infants, from a total score of 6 to 14, from a total score of 8 to 13 and from a total score of 6 to 13. The improvement in sleep quality included more hours of sleep, less frequent waking, less fuss, and when wake up baby looks fresh. The conclusion of this study is massage therapy can improve sleep quality in tuberculosis infants who have sleep disorders.